MANEJO DO FÓSFORO NA FASE INICIAL DE ADOÇÃO DO SISTEMA DE INTEGRAÇÃO LAVOURA-PECUÁRIA EM PLANTIO DIRETO - Galetto, Shivelly Los (2013)
Crop-livestock integration (CLI) is a practice that, when properly managed and associated with no-tillage (NT), has been improving a soil quality. However, most of soils in Brazil have a low level of phosphorus (P). Thus, the development of strategies to increase phosphorus use efficiency has been crucial for sustainable agribusiness in an agronomic and economic viewpoint. The objectives of this study were to evaluate the accumulation of P and yields of corn, soybean, black oat and ryegrass fertilized with sources and levels of P2O5 in CLI under NT and to evaluate the bioavailability of P for maize, extracted by the methods Melich-1 (M1), ion exchange resin (IER) and modified Morgan (MM), after 36 months of experimentation. The experiment was established in April 2009, in the municipality of Castro-PR in a Dystric Cambisol and the experimental design was an incomplete factorial (3x3+1), with four replications. The treatments consisted in surface (total area) application of levels (0, 60, 120 and 180 kg ha-1 yr-1 P2O5) during sowing of winter forage (black oat or annual ryegrass) in the form of triple superphosphate (TSP), reactive rock phosphate (RRP) and magnesium termophosphate (MTP). The dry matter yields for black oat (2009 and 2011) and ryegrass (2010), grain yield for maize (2009/10 and 2011/12) and soybean (2010/11), and P accumulation were evaluated in these crops. In 36 months of study, soil samples were collected from the layers 0-5, 5-10, 10-15 and 15-20 cm, to determine the concentrations of available P by different methods extractants (M1, IER and MM) and to assess the availability of P for maize (2011/12). The use of TSP, during sowing of black oat occasioned the highest yield of dry matter (DM) and P accumulation in DM (P-DM) in this crop. However, for the maize crop, the treatments did not affect grain yield (GY) and P accumulation in plant (P-Ac) at the first year of use. The treatments did not affect the yield of DM annual ryegrass and GY of soybean, in the second year of assessment. However, there was a greater accumulation of P-DM in the annual ryegrass, when applying MTP. For soybeans, the P-Ac was higher in the treatments with early application of TSP and MTP. The application of MTP during sowing of black oat occasioned the highest yield of DM and P-DM in this crop. The GY and P-Ac were higher in maize, occasioned by the use TFM, in the third year of study. Concentrations of available P in soil after 36 months of study, had variations according to each extractor. The ion exchange resin extracted greater amounts of P, followed by the extractor M1 and MM. In the treatments that received application of TSP, the M1 and IER extractants has obtained similar efficiency when correlated with the maize’s attributes (DMY, GY, P-DM and P-Ex). IER was the most efficient extractor which correlated with the P-DM and P-Ex when were applied sources insoluble in water (RRP and MTP). The MM extractor was ineffective to predicting the bioavailability of P for the maize grown in a soil with high content of clay and Fe and Al oxides, which received the application of rates and sources of P in a CLI system under NT.